First-in-human phase 1 dose-escalation results with livmoniplimab, an antibody targeting the GARP:TGF-ß1 complex, as monotherapy and in combination with the anti–PD-1 antibody budigalimab in patients with advanced solid tumors - Shimizu, Toshio; Powderly, John; Abdul Razak, Albiruni; LoRusso, Patricia; Miller, Kathy D.; Kao, Steven; Kongpachith, Sarah; Tribouley, Catherine; Graham, Michelle; Stoll, Brian; Patel, Maulik; Sahtout, Mohammad; et al. (Frontiers in Oncology, 2024)
BackgroundTransforming growth factor (TGF)-ß1 is a pleiotropic cytokine that can promote tumor growth and suppress antitumor immune responses. Latent TGF-ß1 associates with glycoprotein-A repetition predominant (GARP) on the surface of regulatory T cells prior to its activation and release. Livmoniplimab is a monoclonal antibody (mAb) that binds the GARP:TGF-ß1 complex to inhibit activation and release of TGF-ß1. It is in clinical development in combination with budigalimab, an anti-programmed cell death protein 1 Fc-modified mAb. The first-in-human, phase 1, dose-escalation results are presented herein (ClinicalTrials.gov: NCT03821935).MethodsThe dose-escalation phase enrolled adult patients with advanced solid tumors. Patients received escalating doses of livmoniplimab ranging from 3mg to 1500mg, once every 2 weeks (Q2W), as monotherapy or in combination with a 500mg fixed dose of budigalimab Q4W. The primary objective of the dose escalation was to determine the recommended phase 2 dose. Secondary objectives were to assess safety and pharmacokinetics (PK), and exploratory objectives included evaluating preliminary efficacy.ResultsFifty-seven patients enrolled in the dose escalation: 23 in monotherapy cohorts and 34 in combination therapy cohorts. Dose-limiting toxicities were limited, no maximum tolerated dose was reached, and the maximum administered dose of 1500mg was selected for dose expansion. The most common adverse events reported in monotherapy-treated patients were fatigue, anemia, and nausea, and those in combination therapy-treated patients were pruritus, fatigue, nausea, and anemia. Livmoniplimab exhibited dose-proportional PK, and peripheral blood biomarker data demonstrated saturation of the GARP:TGF-ß1 complex on platelets at livmoniplimab doses within the linear PK range. No objective tumor responses were observed in the monotherapy dose escalation. However, the objective response rate was 15% in the combination dose escalation, with a median response duration of 8.4 months.ConclusionLivmoniplimab was well-tolerated as monotherapy and in combination with budigalimab in the dose-escalation phase. Encouraging preliminary efficacy was demonstrated in the combination dose escalation in heavily pretreated patients, supporting further development of this novel drug combination in patients with advanced solid tumors.